Giving Voice in a Culture of Silence. From a Culture of Compliance to a Culture of Integrity - Verhezen, Peter (Journal of business ethics, 2010)
This article argues that attempting to overcome moral silence in organizations will require management to move beyond a compliance-oriented organizational culture toward a culture based on integrity. Such cultural change is part of good corporate governance that aims to steer an organization to enhance creativity and moral excellence, and thus organizational value. Governance mechanisms can be either formal or informal. Formal codes and other internal formal regulations that emphasize compliance are necessary, although informal mechanisms that are based on relationship-building are more likely to achieve moral excellence. Such a shift can be viewed as a transformative strategy for overcoming the destructive side effects and business risks of the tendency within corporate cultures to remain mute when faced with issues that violate personal or corporate values. Genuine dialogues and appropriate ethical decision-making training can deepen the understanding and create a mindful awareness (of ethical values) and induce trust that embrace both complying with rules and regulations, as well as inciting creative “ethical innovation” with respect to human interaction in multinational companies.